Technologizing Cultural Consumption: The Tales and the Virtual in the East Asian Andersen - Tam, Kwok-kan (Aktualitet - Litteratur, kultur og medier, 2019)
Most of Andersen’s stories have been translated into Chinese and Japanese for more than 100 years. They are read as children’s literature for values and morals that are universal, but hidden in these values and morals are notions of truth, self-identity and individuality that challenge traditional East Asian concepts of selfhood. Andersen represents new values for East Asian modernity. Tracing the reception of Andersen in East Asia, this paper deals with changes in representation, particularly in recent years with the opening of the Shanghai Andersen Cultural Park, the wide circulation of Andersen stories in animation films in Japan, and the technological representations of culture in the digital age. In this paper, Chinese representations of Andersen will be contrasted with the Japanese so as to understand the different receptions of Andersen in the East Asian context. The recent trend of technologizing Andersen will be discussed in relation to cultural consumption and gamification. Since much of the recent development in technologizing Andersen has to do with visual representation, photos will be provided as illustrations.